'Calibrating to scale: a framework for humanitarian health organizations to anticipate, prevent, prepare for and manage climate-related health risks' - Schwerdtle, Patricia; Irvine, Elizabeth; Brockington, Sonia; Devine, Carol; Guevara, Maria; Bowen, Kathryn J. (Globalization and health, 2020)
Climate Change is adversely affecting health by increasing human vulnerability and exposure to climate-related stresses. Climate change impacts human health both directly and indirectly, through extreme weather events, changing distribution of health risks, increased risks of undernutrition, population displacement, and greater risks of injuries, disease, and death (Ebi, K., Campbell-Lendrum, D., & Wyns, A. The 1. 5 health report. WHO. 2018). This risk amplification is likely to increase the need for humanitarian support. Recent projections indicate that under a business as usual scenario of sustained greenhouse gas emissions, climate change could double the demand for humanitarian assistance by 2050 (World Health Organization. Operational Framework for building climateresilient health systems. WHO. 2015). Humanitarian assistance is currently not meeting the existing needs, therefore, any additional burden is likely to be highly challenging. Global health advocates, researchers, and policymakers are calling for urgent action on climate change, yet there is little clarity on what that action practically entails for humanitarian organizations. While some humanitarian organizations may consider themselves well designed to respond, climate change as a transversal threat requires the incorporation of a resilience approach to humanitarian action and policy responses. By bringing together authors from two historically disparate fields - climate change and health, and humanitarian assistance - this paper aims to increase the capacity of humanitarian organizations to protect health in an unstable climate by presenting an adapted framework. We adapted the WHO operational framework for climate-resilient health systems for humanitarian organizations and present concrete case studies to demonstrate how the framework can be implemented. Rather than suggest a re-design of humanitarian operations we recommend the application of a climate-lens to humanitarian activities, or what is also referred to as mainstreaming climate and health concerns into policies and programs. The framework serves as a starting point to encourage further dialogue, and to strengthen collaboration within, between, and beyond humanitarian organizations.
Gesehen am 16.09.2020